Pengaruh Kualitas Produk, Citra Merek dan Promosi terhadap Keputusan Pembelian Sepeda Motor Yamaha di Kota Batam - Sigalingging, Kesya Agrariani; Wasiman, Wasiman (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
In the increasingly competitive motorcycle industry, companies face the challenge of optimizing product appeal to influence consumer purchasing decisions. This study aims to examine the effect of product quality, brand image, and promotion on consumer purchasing decisions for Yamaha motorcycles in Batam City. Using a descriptive quantitative method, the study collected data from 100 respondents who had purchased Yamaha motorcycles, selected through purposive sampling. Data analysis included validity and reliability tests, classical assumption tests, multiple linear regression, and hypothesis testing using SPSS version 26. The results show that product quality, brand image, and promotion each have a positive and significant impact on purchasing decisions. Specifically, product quality contributes 25.2%, brand image contributes 17.3%, and promotion contributes 45.3% to the variance in purchasing decisions. The overall model explains 86.2% of the variance (Adjusted R² = 0.862), indicating that these three factors are dominant drivers in consumer decision-making. The findings suggest that enhancing product quality, strengthening brand perception, and implementing adaptive promotional strategies are essential for improving consumer purchase behavior in the two-wheeler market, particularly for Yamaha in urban areas such as Batam.